EVALUATION OF BEHAVIOUR-BASED SAFETY AS AN INCIDENT PREVENTION TOOL IN SELECTED CONSTRUCTION COMPANIES IN PORT-HARCOURT - Onubueze, Vincent U; Ugbebor, John E.; Nwoye Selema (International Journal of Innovations in Engineering Research and Technology, 2025)
This research was conducted to evaluate the effectiveness of behavior-based safety (BBS) approach as an incident prevention tool in selected construction companies in Port Harcourt. Analytical cross-sectional research design approach was adopted. Primary data were sourced through administration of a structured questionnaire. The population comprised of 542 workers (70 from small scale, 472 from medium scale company) from which 230 participants were sampled. 230 questionnaires were distributed and only 199 questionnaires were correctly filled and returned representing 86.5% response rate. Data analysis was done using SPSS version 25.0 software and Excel statistics while descriptive statistics and Pearson correlation were used for data analysis. The results of the Pearson correlation analysis showed that there is a significant and positive relationship between BBS and incident prevention because the correlation coefficient r is 0.602 indicating strong positive relationship and p-value is 0.000<0.01indicating significant relationship. This means that continuous improvement in the BBS approach will lead to a great reduction of incidents in construction companies. This suggests that the tendency of occurrence of incidents decreases as BBS rises. Results also reveals that there are some practices and behaviors identified by the BBS approach that might significantly influence incident prevention, as shown by the relatively strong positive association. Methodically collecting and analyzing data on safety behaviors and observations, training and education, employee participation, safety equipment and resources, workload and time pressure, and enhancing safety based on BBS findings were all components of this particular activity. There was a high probability that incidents will rise in the organizations unless these practices are implemented. The study recommended that construction firms should implement a comprehensive BBS program and create a positive safety culture that encourages employees to speak up about safety concerns.